MO498: Incident Chronic Kidney Disease in Older Adults With Diabetes. (3rd May 2022) - Lim, Cynthia; Mong Bee, Yong; Ang, Andrew; Abdul Kadir, Hanis; Liang Kwek, Jia; Choo, Jason; Chuan Tan, Ngiap
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) is a growing global public health burden among aging populations and is associated with increased risks of cardiovascular disease, kidney failure and death. Early identification and treatment can amelioriate these risks. We aimed to evaluate incident CKD and risk factors among older adults with diabetes in Singapore. METHOD: Retrospective cohort study of 13 028 older adults ≥65 years with diabetes mellitus who were free of CKD (eGFR ≥60 mL/min/1.73 m 2 ) at baseline and had kidney function tested 3 years later at Singapore's largest healthcare cluster that includes the Singapore General Hospital and SingHealth Polyclinics. Demographic, clinical and laboratory data were retrieved from electronic medical records and the SingHealth Diabetes Registry. Incident CKD was present if eGFR was <60 mL/min/1.73 m 2 at follow up. Binary logistic regression analysis was used to obtain the odds ratio (OR) and 95% confidence interval (CI) for pre-selected factors. RESULTS: In this multi-ethnic cohort (Chinese 91%, Indian 8%, Malay 8% and other ethnicities 3%), the mean age was 72.1 ± 5.6 years and the eGFR was 84.2 ± 11.1 mL/min/1.73 m 2 . The majority were on glucose and blood pressure lowering medications and achieved glycated haemoglobin (HbA1c), systolic blood pressure (SBP) and diastolic blood pressure (DBP) of 7.1% ± 1.1, 133 ± 16 mmHg and 68 ± 9 mmHg, respectively. Cumulative incident CKD among older adults with diabetes was 19.4% >38.5 ± 4.7 months. In the fully adjusted model, considering age, gender, ethnicity, comorbidities (hypertension, cardiovascular disease, cancer, statin use), SBP, DBP, BMI and laboratory results (eGFR, albuminuria, glucose, HbA1c, LDL- and HDL-cholesterol). Female gender adjusted OR: 1.54, [95% confidence interval (95% CI) 1.36–1.76], Malay ethnicity (adjusted OR: 1.24, 95% CI 1.01–1.53), hypertension (adjusted OR: 1.40, 95% CI 1.02–1.93), albuminuria (adjusted OR: 1.49, 95% CI 1.31–1.69) and higher HbA1c (adjusted OR: 1.11, 95% CI 1.04–1.18/unit increase) were independently associated with incident CKD, while higher eGFR (adjusted OR: 0.88, 95% CI 0.87–0.88/unit increase) and statin use (adjusted OR: 0.79, 95% CI 0.64– 0.99) were associated with decreased incident CKD. CONCLUSION: Incident of CKD was frequent among older adults with diabetes. The presence of risk factors for incident CKD can aid clinicians to identify those who may benefit from close surveillance and interventions.